Diabesity Increases Inflammation and Oxidative Stress - Dayre A; Pouvreau C; Butkowski EG; de Jong B; Jelinek HF (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2016)
Background: Inflammation and oxidative stress are two pathophysiological mechanisms that link obesity, type 2 diabetes mellitus (T2DM) and diabesity. However how levels of inflammatory and oxidative stress markers differ between patients with obesity, T2DM and diabesity has not been completely elucidated.  Objectives: This study aimed to investigate the interactions between emerging biomarkers of oxidative stress and inflammation and the differences in biomarker levels between T2DM, obesity and diabesity in a clinical setting. Methods: A total of 270 patients attending a diabetes health screening clinic (57 T2DM; 37 obese; 44 diabesity, and 132 age, gender, and weight-matched controls) participated in the study. All patients were selected on clinical grounds. Differences in the level of biomarkers of oxidative stress (erythrocyte GSH/GSSG, 8-hydroxy-2-deoxy-guanosine (8-OHdG) and urinary 8-iso-prostaglandin F2α), inflammation (CRP, IL-6, IL-10 and IL1β), and coagulation (C5a, D-dimer) were determined. Results: Both inflammatory markers and oxidative stress differed significantly between the three clinical groups. GSH revealed a significant difference between the T2DM (1456.6 µM/mL ± 737.5, p<0.03) and obese groups (1890.7 µM/mL ± 823.3). 8-OHdG increased significantly in the obese group (185.5ng/mL ± 162.4, p<0.03) compared to the control group (146.8ng/mL ± 127.5). Similarly 8-OHdG was significantly higher in the obesity group (185.5ng/mL ± 162.4) compared to the T2DM group (119.2ng/mL ± 92.9, p<0.03). A significant increase was also found for 8-iso-PGF2α in the diabesity group (2.3 ± 15.0 ng/mL) compared to the control group (1.0 ± 1.9 ng/mL, p<0.03) and the T2DM group (1.1±2.5ng/mL, p<0.05). 8-iso-PGF2α in the diabesity group (2.3±15.0 ng/mL) was significantly higher than the obese group (1.1ng/mL ±1.8, p<0.03). A significant decrease occurred in IGF-1 levels for diabesity (144.6 ± 285.7 ng/mL) compared to the control (302.8 ± 547.2 ng/mL, p <0.03) and the T2DM groups (225.1ng/mL ± 417, p<0.05). A statistically significant increase in the inflammatory marker ratio IL-6/IL-10 between the control group (0.41 ± 0.7) and the obesity group (0.71 ± 1.94, p<0.03) was also observed.  Conclusion: The results obtained indicate that 8-iso-PGF2α, 8-OHdG as markers of oxidative stress and IGF-1, IL-6/IL-10 are associated with diabesity and could be used diagnostically for risk assessment.